PENGARUH MODEL CONCEPT SENTENCE TERHADAP KEMAMPUAN MENULIS DITINJAU DARI GAYA BELAJAR SISWA SMP NEGERI 5 ADIWERNA - Nadiyah Noviana; Maman Suryaman (Universitas Muria Kudus, 2026)
This study aims to determine the effect of the Concept Sentence learning model on the descriptive text writing skills of seventh-grade students at SMP Negeri 5 Adiwerna, in terms of learning styles. This study used a quantitative approach with an experimental method. The research sample consisted of seventh-grade students in E as the experimental group taught using the Concept Sentence model. Data were collected through descriptive text writing tests at the pre- and post-test stages, as well as a learning style questionnaire. Data analysis was performed using a dependent t-test and a one-way ANOVA test after meeting the prerequisite tests for normality and homogeneity. The results showed that there was an increase in students' descriptive text writing skills after implementing the Concept Sentence learning model, as evidenced by post-test scores that were significantly higher than pre-test scores. In addition, the ANOVA test results showed that there were no significant differences in descriptive text writing skills based on auditory, kinesthetic, and visual learning styles. Thus, it can be concluded that the Concept Sentence learning model is effective in improving students' descriptive text writing skills and can be applied evenly without being influenced by differences in learning styles. Keywords: Concept Sentence, writing ability, descriptive text, learning style, junior high school students